Türk iş hukukunda işçinin ücretinin düşürülmesi - Anlama, Adil (My University, 2017)
TÜRK İŞ HUKUKUNDA İŞÇİNİN ÜCRETİNİN DÜŞÜRÜLMESİ “Türk İş Hukukunda İşçinin Ücretinin Düşürülmesi” konulu çalışmamızda, iş hukukunun en temel ve en önemli kavramlarından biri olan ücretin hangi şartlarda ve ne şekilde düşürülebileceği; ücretin düşürülmesi karşısında işçinin korunmasının usul ve esasları incelenmiştir. Çalışmamızda; ücretin düşürülmesine ilişkin mevzuattaki gelişme ve değişikliklere, somut uygulama ve uyuşmazlıklara, yargı kararlarına, konuya ilişkin öğretideki görüşlere yer verilmiş, konu bu çerçevede tartışılarak görüş ve sonuçlara ulaşılmıştır. Çalışmamız üç bölümden oluşmaktadır. Birinci bölümde ücret kavramını, ücret çeşitlerini ve ücretin belirlenmesini ele aldık. İkinci bölümde, bireysel iş hukuku açısından ücretin düşürülmesini ele aldık. Üçüncü bölümde toplu iş hukuku açısından ücretin düşürülmesi konusunu ele aldık. cret, ücretin belirlenmesi, ücretin düşürülmesi, ücrette değişiklik, toplu iş hukuku.

REDUCİNG EMPLOYEE'S WAGE İN TURKISH LABOUR LAW In our study “Reducing Employee's Wage İn Turkısh Labour Law”, the conditions under which and in what conditions the wage, which is one of the most basic and most important concepts of labour law. The procedures and principles of the protection of workers against the reduction of wages have been examined. In our study; the concrete developments and changes REDUCİNG EMPLOYEE'S WAGE İN TURKISH LABOUR LAW In our study “Reducing Employee's Wage İn Turkısh Labour Law”, the conditions under which and in what conditions the wage, which is one of the most basic and most important concepts of labour law. The procedures and principles of the protection of workers against the reduction of wages have been examined. In our study; the concrete developments and changes in the legislation concerning the reduction of the wages, the concrete implementations and disputes, the judicial decisions, the opinions of the doctrine about the subject and the opinions and results were reached by discussing this subject. Our study consists of three parts. In the first part we discussed the concept of wages, the types of wages and the determination of wages. In the second part, we discussed the reducing of wages in terms of individual labour law. In the third part, we have discussed the issue of reducing wages in terms of collective labour law. Wage, determination of the wage, reducing of the wage, changing of the wage, collective labour law.
Keywords: Hukuk; Hukuk ve mevzuat; İş hukuku; Sosyal güvenlik; Türkiye; Ücretler